Portrait of Steve Power being recorded - Meredith, John, 1920-2001. (1984)
"One of the best traditional singers John Meredith has met with, Steve Power is seen recording one of his many songs for the enlightenment of young Australians of the future."--Typed on card enclosed with print.
Title from label on back of print.
This photograph was taken as part of John Meredith's "Real Folk" Australian folklore recording project.
P1/100
Also available online
Keywords: Power, Steve, -- 1914- -- Portraits; Folk singers -- New South Wales -- Portraits; Folk music -- New South Wales